Analysis of the Conformity of Restorative Justice and Diversion Principles in the Juvenile Justice System Law with the Equality Principles of the Convention on the Rights of the Child - Adzana, Ananda Syukria; Muslim, Ikhwanul; Sunariyo, Sunariyo (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study discusses the suitability of the principles of restorative justice and conversion stipulated in the Juvenile Justice Act (UU SPPA) with the principle of equality in the Convention on the Rights of the Child. The approach used in this study is normative law to analyze the various legal regulations in Indonesia, such as Law No. 11/2012 concerning the Juvenile Criminal Justice System and the Convention on the Rights of the Child. The target of this study is to review the concept of restorative justice and the principle of diversion and assess their consistency with the principle of equality stipulated in the Convention on the Rights of the Child. This study uses two theories, namely the theory of restorative justice and equality. The results of the study indicate that the principles of restorative justice and diversion in the UU SPPA aim to provide protection and justice for children in conflict with the law. Both principles focus on child welfare and encourage a humane approach in resolving child crimes. In addition, these principles are consistent with the principle of equality in the Convention on the Rights of the Child, especially with Articles 2 and 40 paragraph (1).